An Underestimated Diagnosis in Practice: Wernicke Encephalopathy in Two Patients With Cancer - (:unkn) unknown (My University, 2017)
Kanser hastalarında şuurda bozulma oldukça sık görülür. Bu durumun en sık sebepleri enfeksiyonlar, metabolik bozukluklar, organ hasarları, ilaçlar, deliryum ve santral sinir sistemine metastazlardır. Wernicke Ensefalopatisi (WE) tanısı bu özel hasta grubunda alkolik olmayan diğer vakalarda olduğu hemen akla gelmez. Bu yazının amacı WE ve kanser birlikteliğine dikkati çekmek ve Manyetik Rezonans Görüntülemenin (MRG) bu kompleks hastalıktaki önemini vurgulamaktır. Biz şuurda bozulma nedeniyle kliniğimize danışılmış 2 hastayı sunduk. Hastalara ayırıcı tanılara yaklaşım açısından beyin MRG yapıldığında, simetrik orta hat lezyonları WE tanısını şüphelendirdi. Hastalardan birinin MRG'sinde alkolik olmayan WE vakalarında görülen şekilde kortikal ve serebellar lezyonlar da mevcuttu. Tiamin tedavisi sonrasında 4-8 hafta içerisinde, her iki hasta klinik ve radyolojik olarak düzelme gösterdi. Şuur bulanıklığı ile başvuran kanser hastalarında WE tanısı akılda tutulmalıdır. Geriye dönüşsüz sekelleri önlemek amacıyla tiamin tedavisi ivedilikle başlanmalıdır. İyi tanınan radyolojik görünümler alkolik olmayan hastalarda da erken tanı ve efektif tedavinin önünü açacaktır.

Impairment of mental status is frequently seen in cancer patients. Common causes are infection, metabolic disturbance, organ failure, medication, delirium or metastatic disease. Wernicke encephalopathy (WE) is likely to be underestimated in clinical practice in nonalcoholic population including this special patient group. The purpose of this paper is to take attention to WE and cancer concomitance, and emphasize the role of magnetic resonance imaging (MRI) in the early diagnosis of this complicated disease. We report two cancer patients who were consulted to our neurology department because of altered mental status and other neurological disabilities. When the patients underwent brain MRI for differential diagnosis, symmetrical perimidline lesions of the brain made the suspicion of WE diagnosis. In addition, one of the patient's MRI showed symmetric cortical and cerebellar involvement that is more typical in nonalcoholic form of WE. Both patients mostly recovered clinically, also showed concordant resolution of MRI abnormalities within 4-8 weeks after thiamine supplementation. WE diagnose should be kept in mind in cancer patients with altered mental status and thiamine treatment should be started during undergoing evaluation and differential diagnose to prevent irreversible clinical sequelae. Improved recognition of radiologists and well-known imaging findings of WE can facilitate early detection and effective treatment in nonalcoholic WE patients.
Pratikte Gözardı Edilen Bir Tanı: Kanser Hastalarında Wernicke Ensefalopatisi
Keywords: Geriatri ve Gerontoloji; Hematoloji; Tıbbi Araştırmalar Deneysel